2019
DOI: 10.1111/cdev.13206
|View full text |Cite
|
Sign up to set email alerts
|

Third‐Party Sociomoral Evaluations in Children With Autism Spectrum Disorder

Abstract: We examined explicit and implicit processes in response to third-party moral transgressions in children with autism spectrum disorder (ASD). Twenty 4-to 7-year-old children with ASD and 19 typically developing controls evaluated dynamic visual stimuli depicting intentional or accidental harm to persons or damage to objects. Moral evaluations, eye fixations, and pupil dilations toward the stimuli were collected. Results indicate a preserved capacity to understand the mental states of perpetrators and an implici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
4
10
0
Order By: Relevance
“…Our finding of atypical moral decision-making in a significant portion of the ASD group supports hypothesis 1, and is consistent with previous ASD literature (Gleichgerrcht et al, 2013; Li et al, 2019; Moran et al, 2011; Rogé & Mullet, 2011; Salvano-Pardieu et al, 2016; Schneider et al, 2013). Given the overall trend towards equity in the ASD group, it is possible that the subgroup of equal allocators were developmentally delayed in terms of their ability (ToM) to use and integrate social information in moral decision-making.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding of atypical moral decision-making in a significant portion of the ASD group supports hypothesis 1, and is consistent with previous ASD literature (Gleichgerrcht et al, 2013; Li et al, 2019; Moran et al, 2011; Rogé & Mullet, 2011; Salvano-Pardieu et al, 2016; Schneider et al, 2013). Given the overall trend towards equity in the ASD group, it is possible that the subgroup of equal allocators were developmentally delayed in terms of their ability (ToM) to use and integrate social information in moral decision-making.…”
Section: Discussionsupporting
confidence: 93%
“…However, these findings are not consistent throughout the literature as there is evidence for contrary results (Blair & James, 1996; Leslie et al, 2006; Patil et al, 2016; Sally & Hill, 2006). For example, new and advanced research measuring both explicit (verbal) and implicit (eye-tracking) responses has revealed that children with ASD are in fact able to understand a perpetrator’s intention in making third-party judgements (Li et al, 2019). However, they demonstrated milder (less negative) explicit judgements and had an atypical response pattern characterised by increased sensitivity to damaged objects rather than hurt people.…”
Section: Theory Of Mind and Moral Decision-making In The Context Of Autism Spectrum Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Garon et al (2018) found that during moral dilemmas pupil dilation in ASD and TD groups is similar, even though individuals in the ASD group seemed to have more difficulty understanding the dilemma and produced fewer socially adaptive moral decisions. Moral judgements were made similarly by children with ASD and the TD group in the study by Li et al (2019) and both groups showed similar increases in pupil dilation in response to moral reasoning, however some patterns in the ASD group were remarkable. The children with ASD evaluated damage to an object as worse than damage to a person and this was also reflected in larger pupil dilation to damaging an object, which might be an effect of a special interest in object, according to Li et al (2019) 3.4.3.5.…”
Section: Processing Of Emotional Informationmentioning
confidence: 65%
“…Immaturity of perceptual processing can influence task results with complex stimuli in younger subjects (Laeng et al, 2018). In children with ASD, specific interests in objects are more present at a younger age, so younger children might have different moral judgments and stronger pupillary responses to damage to objects than older children (Li et al, 2019). In many of the included studies, the participants' age range is wide, so there are not enough participants in the same small age interval to differentiate between intervals.…”
Section: Subject-dependent Influencesmentioning
confidence: 99%